Debt priority structure, market discipline, and bank conduct - Danisewicz, Piotr; McGowan, Danny; Onali, Enrico; Schaeck, Klaus (Oxford University Press, 2017)
We examine how debt priority structure affects bank funding costs and soundness. Leveraging an unexplored natural experiment that changes the priority of claims on banks’ assets, we document asymmetric effects that are consistent with changes in monitoring intensity by various creditors depending on whether creditors move up or down the priority ladder. The enactment of depositor preference laws that confer priority on depositors reduces deposit rates but increases nondeposit rates. Importantly, subordinating nondepositor claims reduces bank risk-taking, consistent with market discipline. This insight highlights a role for debt priority structure in the regulatory framework.